HUBUNGAN PENGETAHUAN DAN PERILAKU PETUGAS CLEANING SERVICE DENGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DALAM PENANGANAN LIMBAH MEDIS PADAT DI RSUD KOLONODALE KABUPATEN MOROWALI UTARA - Uljannah, Uljannah; Muh. Khadafi; Andi Yusuf (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Solid medical waste is a source of infection risk in hospitals, which can endanger the health of cleaning staff. The use of complete personal protective equipment (PPE) is the primary preventative measure to minimize this risk. However, compliance with PPE use is often influenced by internal factors, such as staff knowledge and attitudes. Therefore, this study was conducted to analyze the relationship between knowledge and attitudes and behavior regarding PPE use in solid medical waste management at Kolonodale Regional Hospital, North Morowali Regency. This study used a cross-sectional study design with 41 cleaning staff as respondents. The research instrument was a structured questionnaire that measured knowledge, attitudes, and behavior regarding PPE use. The results showed a significant relationship between knowledge (p-value 0.007) and attitudes (p-value 0.001) of cleaning service staff regarding solid medical waste management and PPE use. Knowledge and attitudes have been shown to be significantly associated with PPE use among cleaning service personnel handling solid medical waste at Kolonodale Regional Hospital. Compliance can be improved through ongoing education, occupational safety training, supervision, and strengthening a safety culture within the hospital environment.